Response to Article “Ultrasensitive Hierarchical AuNRs@SiO2@Ag SERS Probes for Enrichment and Detection of Insulin and C-Peptide in Serum” [Response to Letter] - Zhang T; Wu H; Qiu C; Wang M; Wang H; Zhu S; Xu Y; Huang Q; Li S (International Journal of Nanomedicine)
Tong Zhang,1–3,* Han Wu,1,2,* Chenling Qiu,1,2 Mingxin Wang,1,2 Haiting Wang,1,2 Shunhua Zhu,1,4 Yinhai Xu,2 Qingli Huang,1,4 Shibao Li1,2 1Medical Technology School of Xuzhou Medical University, Xuzhou, Jiangsu, 221000, People’s Republic of China; 2Department of Laboratory Medicine, Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, 221000, People’s Republic of China; 3Chuzhou Center for Disease Control and Prevention, Chuzhou City, Anhui, 239000, People’s Republic of China; 4Public Experimental Research Center of Xuzhou Medical University, Xuzhou City, Jiangsu, 221004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qingli Huang; Shibao Li, Email qlhuang@xzhmu.edu.cn; sdjnshlb@xzhmu.edu.cn